Polluted Job Search: The Impact of Poor Air Quality on Reservation Wages - Mariët Bogaard; Steffen Künn; Juan Palacios; Nico Pestel (Institute of Labor Economics (IZA), 2024)
This paper investigates the impact of air pollution on reservation wages. We use rich survey data on unemployed job seekers in Germany and exploit variation in individual exposure to fine particulate matter (PM10) based on the quasi-random allocation of interview slots to individuals. Our results show that an increase in PM10 by one standard deviation (corresponding to 12 μg/m3) reduces the reservation wage by approximately 1.2%. We further provide evidence that PM10 pollution decreases job seekers' search effort, risk tolerance and patience, which serve as potential mechanisms through which PM10 exposure negatively affects the reservation wage of unemployed job seekers.
Keywords: Q53; J64; 330; reservation wage; air pollution; job search